1998
DOI: 10.1165/ajrcmb.18.2.3008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Retinoblastoma Gene Inactivation in the Spectrum of Neuroendocrine Lung Tumors

Abstract: The retinoblastoma (RB) gene plays a key role in cell cycle control by regulation of G1 growth arrest. This gene is inactivated in some human cancers and in most small-cell lung carcinoma (SCLC) cell lines. The aim of this study was to analyze the mechanisms of RB silencing in freshly excised neuroendocrine (NE) tumors embracing the entire spectrum of NE lung neoplasms (typical and atypical carcinoids, large-cell neuroendocrine carcinomas [LCNECs], and SCLCs). To study the role and mechanism of RB inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…21,23 Repeated studies have shown that carcinoid tumors were genetically divergent from high-grade large-cell neuroendocrine carcinoma and small-cell carcinoma, and had no, or only occasional, genetic events such as p53 mutation and Rb inactivation. 13,14,[24][25][26][27][28] In the present study, we demonstrated for the first time that cyclin B1 overexpression was also a very frequent event in high-grade neuroendocrine tumors and was found in most (84%) large-cell neuroendocrine carcinomas and small-cell carcinomas, while no typical carcinoid and only one (20%) atypical carcinoid overexpressed cyclin B1, indicating that regulation of cyclin B1 expression and G2/M arrest are consistently compromised in high-grade pulmonary neuroendocrine tumors, but are intact in typical carcinoid or only occasionally compromised in atypical carcinoid. The high frequency of cyclin B1 dysregulation in both the large-cell neuroendocrine carcinoma and small-cell carcinoma may reflect a similar alteration in cell cycle regulation at the G2/M transition, despite their distinct morphologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,23 Repeated studies have shown that carcinoid tumors were genetically divergent from high-grade large-cell neuroendocrine carcinoma and small-cell carcinoma, and had no, or only occasional, genetic events such as p53 mutation and Rb inactivation. 13,14,[24][25][26][27][28] In the present study, we demonstrated for the first time that cyclin B1 overexpression was also a very frequent event in high-grade neuroendocrine tumors and was found in most (84%) large-cell neuroendocrine carcinomas and small-cell carcinomas, while no typical carcinoid and only one (20%) atypical carcinoid overexpressed cyclin B1, indicating that regulation of cyclin B1 expression and G2/M arrest are consistently compromised in high-grade pulmonary neuroendocrine tumors, but are intact in typical carcinoid or only occasionally compromised in atypical carcinoid. The high frequency of cyclin B1 dysregulation in both the large-cell neuroendocrine carcinoma and small-cell carcinoma may reflect a similar alteration in cell cycle regulation at the G2/M transition, despite their distinct morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,25,[27][28][29] On the other hand, divergence in chromosomal aberrations was also observed between them, 30 and the specific genetic alterations for either large-cell neuroendocrine carcinoma or small-cell carcinoma remain to be further characterized. In the present study, both large-cell neuroendocrine carcinoma and small-cell carcinoma showed almost equally frequent Rb pathway aberration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between E2F1, p53, pRb and hp14 ARF status in lung carcinoma Status of p53, pRb and hp14 ARF had been previously analysed in this series of tumours (Brambilla et al, 1993;Gazzeri et al, 1994Gazzeri et al, , 1998aGouyer et al, 1998). In these tumours, pRb function was inactivated, either by loss-of-function mutations or p16 INK4a loss and/or cyclin D1 overexpression in 29/36 (80%) NE tumours and 18/22 (82%) NSCLC respectively.…”
Section: Overexpression Of E2f1 Correlates With Upregulation Of Some mentioning
confidence: 94%
“…pRb pathway is di erentially disrupted in NSCLC and high grade NE tumours. Whereas loss of pRb protein expression (through mutations and/or loss of transcription) occurs in 85% of SCLC and LCNEC (Gouyer et al, 1998), pRb function is abolished in 85% of NSCLC either through loss of p16 INK4a protein expression (Xu et al, 1996;Gazzeri et al, 1998a), and/ or cyclin D1 overexpression (Brambilla et al, 1997). As E2F1 is one key component of these two pathways (O'Connor et al, 1995;Bates et al, 1998;Kowalik et al, 1998), any alterations a ecting them, especially pRb inactivation, are thought to deregulate its activity.…”
Section: Introductionmentioning
confidence: 99%